Hedgerows for Hedgehogs and Campus Biodiversity - Glen Cousquer; Emily Norris; Peter Lurz; Elizabeth Vander Meer; John Gurnell (Journal of Awareness-Based Systems Change, 2024)
Across society, organisations find themselves challenged to address the climate and nature emergencies.  Universities have a complex set of responsibilities given that they are preparing students for an uncertain future in which the very survival of life is in the balance.  A characteristic of this complex challenge is the need to develop the necessary ecological and vertical literacy required to tackle the many aspects of fragmentation we are subject to.  The 30x30 biodiversity challenge provides universities with an opportunity to address one particular form of fragmentation, that affecting habitats.